Antithrombotic Medication and Major Complications After Mechanical Aortic Valve Replacement - Björn Rikhard; Lehto Joonas; Malmberg Markus; Anttila Vesa; Airaksinen KE Juhani; Gunn Jarmo; Kiviniemi Tuomas (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2025)
Patients with mechanical aortic valve replacement (AVR) require lifelong vitamin K antagonist (VKA) therapy for stroke and systemic embolism prevention. However, VKA treatment predisposes patients to various types of bleeding. In the present study, we sought to assess the success of antithrombotic therapy and the occurrence and timing of strokes and bleeding events after mechanical AVR. A total of 308 patients who underwent isolated mechanical AVR were included in the study, and follow-up data were completed for 306 patients (99.4%). The median follow-up time was 7.3 (interquartile range 4.2 to 10.9) years. The risk for major bleeding was 5-fold compared with major stroke (6.2% vs 1.3% and 20.9% vs 4.0%, respectively; events rates 3.1 vs 0.5 per 100 patient-years, respec-tively) at 30-day and long-term follow-up, indicating good efficacy but inadequate safety of stroke prevention. At the time of the early postoperative major bleeding, the interna-tional normalized ratio was under the therapeutic range in 73.7% of the patients. How-ever, most patients were on triple antithrombotic treatment consisting of subcutaneous enoxaparin, VKA, and a tail effect of discontinued aspirin. During the long-term follow-up, the most common site of bleeding was gastrointestinal (41.7%), followed by genitouri-nary bleeding (23.3%) and intracranial hemorrhage (18.3%). Furthermore, mortality was relatively high, with a 10-year survival estimate of 78.3%. In conclusion, although ische-mic stroke is a well-identified adverse event after mechanical AVR, it seems that major bleeding is a frequent clinically relevant complication during perioperative and long-term follow-up. This finding underscores the recognition and management of modifiable bleed-ing risk factors.
2023 The Author(s). Published by Elsevier Inc.
This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/) (Am J Car-diol 2023;204:185-194)